Inflation in Poland under state-dependent pricing - Pawel Baranowski; Mariusz Gorajski; Maciej Malaczewski; Grzegorz Szafranski (Aboa Centre for Economics (ACE), 2013)
We analyse the short-term dynamics of Polish economy with a prominent state-dependent pricing mechanism of Dotsey, King and Wolman (1999). We compare macroeconomic evidence of price rigidity in a small-scale DSGE model with a state-dependent Phillips curve (SDPC) derived by Bakhshi, Khan and Rudolf (2007) to a benchmark model including hybrid New-Keynesian Phillips Curve (NHPC) of Gali and Gertler (1999). To analyse monetary policy transmission mechanism we estimate both models with Bayesian techniques and focus on the comparison of distribution of price vintages, a degree of price stickiness, values of parameters in Phillips curve equations, and impulse responses to macroeconomic shocks. The estimated state-dependent pricing model generates a median duration of prices about 4 quarters compared to 8 quarters in a time-dependent model. In the state-dependent pricing model it takes more time to dampen inflation dynamics after a monetary policy relative to a time-dependent counterpart. The menu cost model is also able to identify higher variance of technology shocks, and higher persistence in preference shocks, while the dynamics of the impulse responses in time- and state-dependent pricing models are hard to distinguish.
Keywords: E31; 330; state-dependent pricing; inflation; menu costs; monetary policy; Polish economy